Characterizing common bottlenose dolphin (Tursiops truncatus) ecology aspects in the central coast of Peru: Distribution, group dynamics, skin lesions and behavior patterns - Cortez-Casamayor, Sarai; Guidino, Chiara; Silva, Sebastián; Gubbins, Salvador; Campbell, Elizabeth; Pacheco, Aldo S. (Revista de Biología Marina y Oceanografía, 2024)
Despite being a conspicuous species on the Peruvian central coast (~12°S), limited information exists about the population status of common bottlenose dolphins (Tursiops truncatus) in this region. Observations were made from navigation surveys during the austral autumn and spring of 2021 to contribute with new knowledge. Fifty-two individuals were photo-identified and characterized as coastal ecotypes. Twenty individuals were re-sighted between the two seasons, suggesting a continuous presence of these recaptured individuals throughout the study period. Also, skin lesions on the bottlenose dolphins are described from the photo analysis. Dolphin groups had a mean size of 12.7 individuals (SD= 7.7) and were found at a mean distance of 391 m (SD= 229.5) from shore and a mean depth of 6.7 m (SD= 0.39). Groups were formed mainly by adults and juveniles, and their predominant behavior was milling. The description of the ecological and behavioral aspects, as well as the occurrence of common bottlenose dolphins confirms the importance of this habitat for the species.